The Role of Glaciers in the Hydrologic Regime of the Amu Darya and Syr Darya Basins - Alford, Donald; Kamp, Ulrich; Pan, Caleb (World Bank, Washington, DC, 2016)
The headwaters of the Amu Darya and Syr Darya in the western Tien Shan, Pamir and Hindu Kush mountains are a major source of stream flow into the Aral Sea Basin. The water security—affecting energy and food security—of this region and the consequent regional dynamics and politics are connected to these headwaters. Recent concerns related to climate change, glacier retreat and stream flow from these mountains have served to illustrate the very limited understanding that exists concerning the hydrologic regimes of the mountain headwaters of these major river systems as well as of the glaciers, that are a component of those regimes. A better understanding of these hydrologic processes is critical for assessing the amount and timing of water supply and hydropower available (both current and future) for the various countries in the Central Asia region that have headwaters originating in these mountains. Such an understanding is also critical in making estimates of runoff changes under a climate change future. This is the main objective of this study.